EFEKTIFITAS IMPLEMENTASI PENGELOLAAN DANA DESA BERDASARKAN PERMENDAGRI NOMOR 20 TAHUN 2018 TENTANG PENGELOLAAN KEUANGAN DESA DI DESA TATENGESAN - Steven Tarore; Mary Vanye Sandag (STIA MALANG, 2022)
In terms of village finances, the village government is required to prepare a Report on theRealization of the Implementation of the Village APB and an Accountability Report on the Realizationof the Implementation of the Village APB. This report is generated from a village financial managementcycle, starting from the planning and budgeting stages; implementation and administration, toreporting and accountability for village financial management. This research uses qualitative research,primary data is collected through interview techniques, and is supported by secondary data, namelydocumentation. Analysis of the research data uses an interactive model consisting of